Detection of abnormal left ventricular wall movement during isovolumic contraction and early relaxation. Comparison of echo- and angiocardiography. - Doran, J H (1978)
Abnormal left ventricular wall movement during isovolumic contraction and early relaxation was assessed from simultaneous apex and echocardiograms in 50 patients with ischaemic heart disease, and compared with estimates from the corresponding digitised left ventriculograms. During isovolumic contraction, a normal angiogram was accompanied by normal apex-dimension relations in 13 out of 14 cases. In 19 cases, there was angiographic evidence of discrete outward wall movement during isovolumic contraction which was associated with abnormal apex-dimension relations in 15. During isovolumic relaxation, of 14 cases who were normal angiographically, apex-dimension relations were normal also in 11, which in 36 patients with abnormal wall movement on angiogram, apex-dimension relations were abnormal in 30. Correlation was less good between echocardiographic and angiographic estimates of left ventricular minor dimension (r = 0.75), and was absent between those of peak rates of dimension change during systole and diastole. Asynchronous onset of inward wall movement and the distribution of regional abnormalities of overall wall movement amplitude were unrelated to apex-dimension relations. The apex-dimension relation is thus a sensitive and specific means of detecting abnormalities of left ventricular wall movement during isovolumic contraction and early relaxation, unaffected by other manifestation